Willed ambiguity: An exploratory study of sexual misconduct affecting sexual minority male university students in Canada. (December 2021) - Namaste, Viviane; Gaspar, Mark; Lavoie, Sylvain; McClelland, Alexander; Sims, Emily; Tigchelaar, Alex; Dietzel, Christopher; Drummond, JD
We offer exploratory reflections on the matter of sexual misconduct affecting sexuality minority male students by males in positions of authority in the university, based on interviews with eight sexual violence service providers and five men across Canada with lived experience, as well as information gathered through our recruitment work. Data were interpreted using thematic analysis. Our results indicate that there is a need to think through the specificity of sexual misconduct involving men in university settings. Several dynamics operate to perpetuate a willed ambiguity on this issue that allow abuses of power to go unchecked. These include difficulties in having a conversation on this topic, the sexualization of gay male culture, gender dynamics among gay men, 'queer' justifications, risks of social isolation, and financial precarity.